2013
DOI: 10.1371/journal.pone.0056187
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome Deficiency Modifies the Alternative Pathway of NFκB Signaling

Abstract: Immunoproteasome is a protease abundant in immune cells and also present, albeit at lower concentrations, in cells outside the immune system. Recent evidence supports a novel role for the immunoproteasome in the cellular stress response potentially through regulation of NFκB signaling, which is the primary response to multiple stressors. The current study tests whether the Classical or Alternative Pathways are regulated by immunoproteasome following chronic TNFα exposure in cultured retinal pigment epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…While free IB␣ can indeed be degraded in a ubiquitin-independent fashion (Mathes et al, 2008) this degradation pathway might not be representative for the canonical ubiquitin-dependent degradation of NF-B-bound IB␣ via the 26S proteasome. In contrast, a recent report by Maldonado and colleagues found that activation of the canonical pathway was not affected in LMP2 −/− and L7M −/− cells while the alternative pathway seemed to be "aberrant" in LMP2 −/− cells (Maldonado et al, 2013). Furthermore, it has been proposed that the immunoproteasome has a higher capacity to clear ubiquitylated proteins accumulating after stimulation with IFN-␥ (Seifert et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While free IB␣ can indeed be degraded in a ubiquitin-independent fashion (Mathes et al, 2008) this degradation pathway might not be representative for the canonical ubiquitin-dependent degradation of NF-B-bound IB␣ via the 26S proteasome. In contrast, a recent report by Maldonado and colleagues found that activation of the canonical pathway was not affected in LMP2 −/− and L7M −/− cells while the alternative pathway seemed to be "aberrant" in LMP2 −/− cells (Maldonado et al, 2013). Furthermore, it has been proposed that the immunoproteasome has a higher capacity to clear ubiquitylated proteins accumulating after stimulation with IFN-␥ (Seifert et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Ultimately depending on the proteasome for activation, NF-B is an important transcription factor in inflammatory conditions. Still, previous studies concerned with the effect of immunoproteasome subunits on NF-B activation yielded contradictory results Faustman, 2000, 1999;Hensley et al, 2010;Kessler et al, 2000;Maldonado et al, 2013;Visekruna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Interestingly, local intramuscular inhibition of proteasome in murine and canine animal models of DMD leads to dystrophin rescue and DGC proteins expression. 7,[9][10][11] The immune cytokine interferon gamma (IFN-γ) can induce the expression of three other catalytically active β-subunits of the 20S proteasome -β1i (PSMB9), β2i (PSMB10), and β5i (PSMB8) to form the induced-proteasome, also referred as immunoproteasome (i-proteasome). 6 i-proteasome is involved in the generation of peptides presented by the MHC-I to the antigen receptors of cytotoxic T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Under basal conditions, the immunoproteasome exists at low concentrations, roughly contributing 5% to the total proteasome population in skeletal muscle [15]. The immunoproteasome is well-known for its role in immune function, specifically generation of antigenic peptides [16] as part of immune surveillance [1719]. Interestingly, under catabolic conditions such as aging [20,21], muscular dystrophy [22], and denervation [11], the immunoproteasome increases, which suggests a link between atrophy and the immunoproteasome may exist in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%